Synthesis and Characterization of Zinc Sulphide (ZnS) Thin Film Nanoparticle for Optical Properties - Abdullah Hasan Jabbar (Journal of Global Pharma Technology, 2018)
ABSTRACT. In this paper, we studied the synthesis and optical features of non-conventional energy have led us to this work. Neat Zinc sulfide (ZnS) powder was hired for synthesizing ZnS thin films. 0.5 µm thickness thin films of the ZnS was deposited by a thermic volatility system onto oxidized Si substrates at the cool temperature (T cold = –50ºC) and at the temperature (T ambient = 25ºC). An individual substrate possessor with a thermo-electric cooler was used to cool the substrates, these deposited ZnS thin films were subjected to air annealing at temperatures 100 oC, 200 oC and 300 oC for one hour in a furnace. ZnS synthesis by precipitation technique. UV-Vis spectroscopy and (SEM) scanning electron microscopy used for the study of optical features. Optical features of ZnS thin films were perfected by measuring the absorbance of ZnS films on glass substrates in the range of wavelength 200–900 nm by subtracting the glass substrate as a reference. ZnS thin films used for optical applications.